QUALIDADE E MOBILIDADE DA MATÉRIA ORGÂNICA DE SISTEMAS ADJACENTES À LAGOA DE CIMA, CAMPOS DOS GOYTACAZES - RJ - Ribas, L. M.; Baldotto, M. A.; Canellas, L. P.; Rezende, C. E. (Geochimica Brasiliensis, 2012)